2023
DOI: 10.29228/eng.pers.68466
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the use of fuel cell hybrid systems for different purposes

Abstract: With the increase in global energy demand, air pollution becoming uncontrollable does not fall off the agenda. It is inevitable to use and spread of renewable energy sources to make energy production cleaner, more reliable and sustainable. In studies for this purpose, the use of fuel cell systems comes to the forefront thanks to its many advantages. The use of hybrid systems is becoming more common day by day in order to minimize the efficiency losses that may occur in the energy production, use and waste mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…In the early years, hydrogen engines had a low power density and low thermal efficiency. Additionally, there were few hydrogen supply systems and hydrogen fueling infrastructure, leading to a lack of large-scale commercial application of hydrogen engines. In recent years, with the application of a series of advanced hydrogen engine technologies and the continuous improvement of the hydrogen energy infrastructure, research on hydrogen engines has gradually increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early years, hydrogen engines had a low power density and low thermal efficiency. Additionally, there were few hydrogen supply systems and hydrogen fueling infrastructure, leading to a lack of large-scale commercial application of hydrogen engines. In recent years, with the application of a series of advanced hydrogen engine technologies and the continuous improvement of the hydrogen energy infrastructure, research on hydrogen engines has gradually increased.…”
Section: Introductionmentioning
confidence: 99%
“…The development of alternative fuels has proven to be an effective method to reduce carbon emissions. Compared with hydrocarbon fuels, hydrogen does not contain carbon, and there are no carbon emissions when hydrogen is used as fuel. Additionally, hydrogen boasts abundant sources, a high calorific value, rapid flame propagation, good knock suppression ability, and low pollutant emissions. For these reasons, hydrogen is an excellent alternative fuel for ignited internal combustion engines and is recognized as one of the best potential zero-carbon emission energy sources for vehicle engines in the 21st century. Transforming a gasoline engine into a hydrogen engine is as simple as installing a hydrogen storage and injection system, along with a cold spark plug, making it an important technical pathway for promoting the upgrading of traditional engine technology .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the development of electric vehicles, the increase in production and usage rates, and the increase in hydrogen fuel production have shown that PEM fuel cells that use hydrogen as fuel can be widely used in electric vehicles in the future. The use of PEM fuel cell electric vehicles (PEMFCEVs) contributes greatly to reducing greenhouse gases in the transportation sector [8]. Because instead of the dirty emissions released by internal combustion engines, only pure water is released as a byproduct of the electrochemical reaction between hydrogen and oxygen.…”
Section: Introductionmentioning
confidence: 99%